A scoping review of healthcare effectiveness data and information set (HEDIS) substance use disorder measures - Oliver Ethan Goal; Isca Amanda; Cameron Adams; Maria Adela Grando (Annals of Medicine)
Introduction:  There is a need to assess the delivery of interventions to improve substance use disorder (SUD) treatment, as measured by the Healthcare Effectiveness Data and Information Set (HEDIS®) metrics. The goal was to characterize published articles reporting HEDIS® SUD measures and recommend future work on applying and investigating SUD HEDIS® metrics and their effect on SUD treatments.Materials and Methods: The PRISMA-ScR scoping review protocol was used to find published work and investigate the most common reported baseline characteristics, HEDIS® metric outcomes, and knowledge gaps. Peer-reviewed papers available through PubMed, Academic Search Premier, Elsevier/ScienceDirect, and Medline were searched up to August 14, 2022.Results:  Twenty-eight articles were included after removing 92 duplications. Twenty-five articles were retrospective cohort studies, two were RCTs, and there was a mixed-method study. SUD metrics were studied in diverse settings, including ED, primary care, mental health care, and SUD specialty care. Twenty-seven papers utilized the Initiation and Engagement of Substance Use Disorder Treatment (IET) measure, and 13 had similar data sources, study populations, and authors. Eight papers presented IET results by substance used, primarily alcohol, cannabis, and opioids.Conclusions:  More research is needed on the HEDIS® SUD metrics and their usefulness in informing SUD prevention and treatment, policy, and public health outcomes.